SAT0083 Tooth loss is associated with swollen joints in a cohort of healthy individuals at increased risk of developing rheumatoid arthritis. (23rd January 2014) - Finckh, A.; Müller, R.B.; Möller, B.; Dudler, J.; Kyburz, D.; Walker, U.A.; Von Muehlenen, I.; Bas, S.; Gabay, C.; Dietrich, T.; de Pablo, P.
Abstract : Background: Evidence suggests an association between periodontitis/tooth loss and rheumatoid arthritis (RA). Periodontitis, a common chronic inflammatory process of the tooth supporting tissues, is a major cause of tooth loss; thus, the number of teeth is considered a surrogate marker for periodontitis. Whether periodontitis/tooth loss is associated with joint involvement in healthy individuals at increased risk of developing RA, is unknown. Objectives: To estimate the prevalence of tooth loss, as a proxy for periodontitis, and to evaluate its association with joint involvement in a cohort of FDRs of patients with RA. Methods: The study sample is based on an ongoing, prospective cohort study of healthy FDRs of patients with active RA, who had no established rheumatologic condition themselves at inclusion. Study participants are followed annually to assess the development of signs and symptoms of arthritis. Data collection included smoking status, number of present teeth, weight, height, morning stiffness (MS) lasting more than one hour (during at least 6 weeks), tender and swollen joint counts (TJC28/SJC28) on examination, and blood tests including antibodies (positive RF and/or ACPA) and shared epitope.The primary outcome was SJC28 on examination, dichotomized at presence of at least one swollen joint with no joint swelling as the reference group. The exposure was the number of present teeth at baseline, which was categorized as ≤20, 21-27, 28-31, and 32 teeth. Multivariate regression models were fit to test the association between tooth loss and swollen joints, adjusting for potential confounders such as age, sex, shared epitope, body mass index (BMI) and smoking status. A secondary analysis model with MS as the endpoint was also fit. Results: The cohort included 366 FDRs (73% female, 93% Caucasian), with a mean age of 41 (SD±14) years. 15% were RF and/or ACPA positive. The mean number of teeth reported at baseline was 28 (SD±4). The categories based on number of teeth present at baseline were 6% (≤20 teeth), 20% (21-27), 46% (28-31), and 28% (32 teeth). FDRs with at least one swollen joint on examination had less teeth compared with those with no swollen joints (mean number of teeth 29 vs. 26, respectively; p=0.004). Compared to FDRs with no tooth loss, those in the lowest category of present teeth (<20 teeth) were more likely to have at least one swollen joint on examination (OR 8.1; 95% CI 1.1, 60) and morning stiffness (OR 5.3; 95% CI 1.1, 26), independent of potential confounders. Conclusions: The results from this large cohort of FDRs of patients with RA demonstrate that individuals who have lost teeth are significantly more likely to have at least one swollen joint. While ascertainment of periodontal status is needed to confirm the role of periodontitis in this association, these results suggest that tooth loss is an independent predictor of joint swelling in individuals at increased risk of RA. Longitudinal studies are needed to establish the causal involvement of periodontitis on RA development. Disclosure of Interest: None Declared